Brass instrument teacher training: a practical experience (Orfeu, 2024)
In search of new formative pathwa-ys, this work reports on the proposal of a pedagogical experience conducted in 2018, in the context of a University Ex-tension Course offering for the training of brass instrument teachers. The propo-sal aimed to train teachers on the basis of practical reality and its development was guided by the design of action research, based on the principles of the Musicpeda-gogical Proposal Sing and Dance with Us (hereinafter referred to as PropMpCDG), and on the ideas and didactic resources of Arnold Jacobs (1915-1998). This appro-ach was associated with concepts speci-fic to the Collective Teaching format and the Situated Learning Theory by Lave and Wenger (2006). The offering, considered pioneering and innovative, was provided in both face-to-face and distance formats, successfully achieving its objectives. The course concluded with an original public presentation, namely, a CDG Musicpeda-gogical Recital.
Keywords: brass instrument teacher training; CDG musicpedagogical proposal; CDG Theoretical Model; Arnold Jacobs; Situated Learning